INTERPRETASI AKUNTANSI DARI PERSPEKTIF UMKM BATIK DI KOTA MALANG - Ningsih, Ayu Agus Tya; Gunawan, Tegar (Manajemen & Bisnis Jurnal, 2023)
Abstract. This study intends to investigate how Malang City batik artisans perceive accounting by keeping track of business activity. This study used a qualitative methodology, a natural setting as a data gathering tool, inductive analysis, and a meaning-centered approach. Researchers employed an interpretive paradigm in this investigation. "Simple accounting" is a phenomenon that characterizes the accounting methods used by batik artisans. The definition of accounting reveals that it is a form of bookkeeping that documents company transactions. Even though the accounting employed was not in conformity with generally accepted accounting rules for small firms, the batik craftsmen included in this study understood and used accounting to manage their finances. Some of the batik artisans acknowledge that they still don't have much accounting understanding. Both batik artisans are aware that accounting is the recording of information for both internal and external parties for the purpose of using it later for business decision-making.